PENGUATAN HIZBUL WATHAN PAPUA MENUJU GERAKAN KEPANDUAN YANG BERTUMBUH, UTUH, DAN TANGGUH: Strengthening Hizbul Wathan Papua towards a Growing, Integrated, and Resilient Scouting Movement - Susi Setianusi; Suroto; Wawan Rumaf; Tomi Riyan Hidayat; Nur Hafid (LPPM Universitas Muhammadiyah Papua, 2026)
Character education and the strengthening of national values remain strategic challenges in Papua, a region characterized by complex social, cultural, and geographical conditions. This community service activity aims to strengthen the organizational capacity of Hizbul Wathan in the Papua region as a platform for character education, leadership development, and civic education grounded in Muhammadiyah values. The program was implemented using a participatory approach through organizational capacity building, value internalization, collective reflection, and consolidation of the scouting movement. The methods employed included reflective lectures, focused group discussions, cross-stakeholder dialogues, and organizational consolidation. Data were collected qualitatively through participatory observation, documentation, and systematic recording of discussion outcomes, and were analyzed using descriptive qualitative techniques. The results indicate an increased collective awareness of the importance of trainer cadre development, synergy with Muhammadiyah charitable enterprises, and the development of an inclusive and context-responsive scouting model. This activity confirms that resource limitations are not the primary barrier but rather an opportunity to build a resilient, value-integrated, and sustainable Hizbul Wathan movement in Papua.